The Influence Of Computerized System On Employee Effectiveness At The Population Ofice And Regional Civil Records Of Medan City - Irham Zulpahmi Ginting (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2021)
The rapid development of science and technology today has an influence on all activities carried out by organizations. One of the technologies that can help in the work within the organization is to use a computerized system. By using a computerized system, each office work unit can increase work effectiveness and time efficiency.This study aims to determine how the influence of the computerized system relationship on the effectiveness of the work of employees at the Regional Population and Civil Registry Office of Medan City. In this study, the data were taken and obtained through the distribution of questionnaires, then processed through the analysis of the product moment correlation coefficient and the determinant coefficient analysis, which were then presented in the form of scientific analysis.Based on the results of the study, it was found that the effect of the Computerized System on the effectiveness of the work of employees at the Regional Population and Civil Registry Office of Medan City was in the medium category. This is proven by the calculation of the product moment correlation coefficient of 0.551. Furthermore, by calculating the determinant correlation, the result is 30%. Which means that the effect of the effectiveness of the work of employees at the Office of Population and Civil Registry Regional Medan City 30% is caused by the computerized system, the remaining 70% is influenced by other variables not included in this study.